Financing Illegal Migration - Zhao, Linda. author. aut Link
XI, 160 p.
Keywords: This unique study explores the relationship between informal financial systems, illegal migration and human smuggling. Focusing on Chinese illegal immigrants working in the US, it examines the motivation and patterns of the use of illegal fund transfer systems, providing a revealing insight into the workings of Chinese underground banks.